Financial management training and savings making training for students at al-ghifari orphanage, gamping - Afifah Nur Aini; Steny Maheswara Halim (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
Management is a basic thing that must be owned by every individual because management is a basic thing used in every line of human life, including managing finances. As young people, we are required to understand financial management in order to be able to manage finances well. This service is intended to provide education about the importance of financial management as well as the practice of making savings with the students of the Abu Dzar Al-Ghifari Orphanage, Gamping. The method used in this program is the delivery of materials, discussions, and hands-on practice to make savings. This program is shown to the students of the Al-Ghifari Orphanage, Gamping. This activity was attended by 25 students.